Detection and in vitro metabolism of AOD9604. Issue 1 (10th September 2014) - Cox, Holly D.; Smeal, Stacy J.; Hughes, Cole M.; Cox, James E.; Eichner, Daniel
<x xml:space="preserve">Abstract</x> AOD9604 is a peptide consisting of the C‐terminal fragment of human growth hormone from amino acids 177–191 with an additional tyrosine residue at the N‐terminus of the peptide. It is reported to mimic the lipolytic properties of growth hormone without the diabetogenic side effects. Therefore, AOD9604 may be used as a performance enhancing drug and is banned by the World Anti‐doping Agency (WADA). The peptide is available on several Internet websites and was recently identified in confiscated vials in the USA. To detect abuse of the peptide in athletes, a solid‐phase extraction method was validated in urine with a limit of detection of 50 pg/mL. The method has good linearity, precision (<20%), specificity and recovery (62%). Six potential metabolites of the peptide were identified after incubation of AOD9604 in serum and urine. Quantification of the metabolites in serum identified a single metabolite, consisting of amino acids CRSVEGSCG, which is significantly more stable than the other metabolites or the parent compound. Screening for AOD9604 and the stable metabolite may potentially allow an increased window of detection. Copyright © 2014 John Wiley & Sons, Ltd.